2006
DOI: 10.1017/s1092852900020800
|View full text |Cite
|
Sign up to set email alerts
|

Brain Network Dysfunction in Bipolar Disorder

Abstract: Bipolar disorder is a common psychiatric condition with significant associated morbidity and mortality. Despite its significance, the neurophysiology and neuropathology of this illness is incompletely understood. Recent advances in neuroimaging techniques have helped to begin clarifying these areas. Specifically, bipolar disorder appears to arise from abnormalities within discrete brain networks (eg, the anterior limbic network). The expression of the symptoms of bipolar disorder does not appear to result from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 64 publications
4
70
0
1
Order By: Relevance
“…Noteworthy, data from the same resource indicate that expression levels of CACNA1C, ODZ4 and NCAN in these two areas are also significantly reduced in patients with BD and depression. BA10/46 map to neighbouring frontal and middle frontal regions in the prefrontal cortex and abnormalities in these brain areas have been described in both disorders 30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, data from the same resource indicate that expression levels of CACNA1C, ODZ4 and NCAN in these two areas are also significantly reduced in patients with BD and depression. BA10/46 map to neighbouring frontal and middle frontal regions in the prefrontal cortex and abnormalities in these brain areas have been described in both disorders 30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…15 These fully normalized images were resliced with trilinear interpolation to a final voxel size of 1.5 Â 1.5 Â 1.5 mm 3 . An additional modulation step was also included to ensure that the total amount of GM in each voxel was conserved before and after normalization.…”
Section: Image Processing and Analysismentioning
confidence: 99%
“…[1][2][3] However, these findings have not been consistently replicated. One possible explanation for this variability in neuroimaging findings is the complexity of the BD phenotype due to its polymorphic clinical manifestations and outcome.…”
Section: Introductionmentioning
confidence: 96%
“…Starkstein and colleagues (1987) suggested that the genetic predisposition for mood disorders and focal lesions in areas that are connected to the limbic system in the right hemisphere, or anterior subcortical atrophy, may provide the necessary factors for the developing of the symptoms. Similarly, in primary mania it has been suggested that the emotional disturbance may be a result of the lack of the inhibitory function of the frontal cortex on subcortical limbic structures, through mild abnormalities in these circuits (Adler et al 2006). Hyperintensities found in the subcortical white matter in some individuals with bipolar disorders may indicate diffuse lesions in circuits which are involved in mood regulation (Frey et al 2004).…”
Section: Neuropsychiatric Fi Ndingsmentioning
confidence: 99%